Energy Consumption Analysis, Efficiency Measures and Renewable Energy Investments Towards a Nearly Net-Zero Campus: The Case Study of Cyprus International University - Akhgar Mohsen; Soyer Emre; Abbasoglu Serkan (Universitas Diponegoro, 2023)
According to the International Energy Agency, energy and process emissions from buildings are responsible for nearly 33 % of global CO2 emissions in 2021; with two other leading sectors; transportation and industry with emissions of 22 % and 30 %, respectively. As a result, parallel with global signs of progress, the topic of energy efficiency and energy management in buildings has come to be a rule of energy policy in Cyprus International University (CIU) buildings. In Cyprus, similar to the reference of IEA, nearly 30% of the energy consumption is from the buildings, which is the most open to energy-saving measures. Since 2017, Sustainable Energy Research Centre in CIU has been working on the energy measures of CIU on both supply and demand sides. To increase the university’s sustainability further in the Energy and Climate section of both UI GreenMetrics and contribution to UN Sustainable Development Goals, conscious energy steps are taken both in energy saving and alternative renewable energy sources in the whole campus which resulted in making CIU a leading example of a sustainable university campus in the Middle-East as it holds the 3rd place for the most sustainable university campus in the region according to UI GreenMetrics World Sustainable University Ranking in 2022. In this paper, an energy audit study will be presented which evaluates the total energy load and energy-saving potential on campus and propose measures that should be taken. In order to conduct this study, Education and Humanities (EH) Building is taken as the pilot study which considers a detailed audit and actions to minimize energy consumption. Then the findings obtained from this energy efficiency study are generalized to all existing buildings on the campus and the expected effect of energy efficiency attempts is projected. These results are joined with the future alternative energy projects planned on the campus and the roadmap to nearly net-zero campus is discussed at the end of the study.